2020
DOI: 10.3390/jcm9123973
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis: MALDI-TOF Mass Spectrometry Microbiological Diagnosis and Electron Microscopy Analysis; Experience of the 2nd Otorhinolaryngology Clinic of Cluj-Napoca, Romania

Abstract: (1) Background: Chronic rhinosinusitis (CRS) represents a wide range of infectious-inflammatory processes affecting, simultaneously, the nose and paranasal sinuses mucosa. The paper presents outcomes of the investigation of CRS microbiological characteristics in a group of 32 patients. (2) Methods: The purulent samples were collected during functional endoscopic sinus surgery. Agar plates were incubated and examined. All types of colonies were identified using Matrix-Assisted Laser Desorption - Ionisation-Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The distinction between the commensal and pathogenic flora is frequently ambiguous; some microorganisms can be both commensal and opportunistically pathogenic [ 46 ]. In one of our previous studies [ 47 ], we identified several opportunistic agents in the etiology of CRS in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between the commensal and pathogenic flora is frequently ambiguous; some microorganisms can be both commensal and opportunistically pathogenic [ 46 ]. In one of our previous studies [ 47 ], we identified several opportunistic agents in the etiology of CRS in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic techniques are often used to study morphological and structural changes in bacterial biofilms. The matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) is used for characterization of different bacterial biofilms and is recognized as a suitable alternative to microscopic techniques [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this idea, a case of cavernous sinus thrombosis secondary to sphenoid sinusitis has been documented [38]. Presently, employing the MALDI-TOF mass spectrometry method, we are investigating the microbiological flora of patients with NFPA compared to those with other pituitary tumours [39]. It is plausible that erosion of the sellar dura and bony floor, frequently observed in NFPA cases, may facilitate the spread of inflammation or infection.…”
Section: Discussionmentioning
confidence: 99%